Question
upstudy study bank question image url

Let \( f(x)=(x+1)^{2} \) Find a domain on which \( f \) is one-to-one and non-decreasing. Find the inverse of \( f \) restricted to this domain \( f^{-1}(x)=\square \)

Ask by Wade Warren. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The domain where \( f(x) = (x + 1)^2 \) is one-to-one and non-decreasing is \( x \geq -1 \). The inverse function is \( f^{-1}(x) = \sqrt{x} - 1 \) for \( x \geq 0 \).

Solution

We begin with the function f(x) = (x + 1)². To have f be one-to-one and non-decreasing, we need to choose a domain on which the function is monotonic (either always non-decreasing or always non-increasing) and does not repeat values. 1. Observe that f(x) is a parabola that has its vertex where the derivative equals zero. Alternatively, note that the expression is a perfect square and reaches its minimum when x + 1 = 0, i.e. when x = -1. 2. For x ≥ -1, the function is non-decreasing (in fact, it is increasing) because as x increases from -1 onward, (x + 1) increases, and squaring a nonnegative number preserves the order. Thus, the domain on which f is one-to-one and non-decreasing is:   x ∈ [−1, ∞) Now, we find the inverse function f⁻¹(x) for x ≥ 0 (since f(x) = (x+1)² gives outputs in [0, ∞) when x ≥ -1). Start with:   y = (x + 1)² Solve for x:   √y = x + 1         (Since x + 1 ≥ 0 for x ≥ −1)   x = √y − 1 Thus, the inverse function is:   f⁻¹(y) = √y − 1 If we use x as the variable for the inverse function, then:   f⁻¹(x) = √x − 1 This gives the final answer:   f⁻¹(x) = √x − 1, for x ∈ [0, ∞).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To ensure that \( f(x) = (x + 1)^2 \) is one-to-one and non-decreasing, we can restrict the domain to \( x \geq -1 \). In this interval, the function is increasing, and each output corresponds to exactly one input. Now, to find the inverse of \( f \) on this domain, we set \( y = (x + 1)^2 \). Solving for \( x \), we get: 1. Take the square root: \( \sqrt{y} = x + 1 \) (and since we’re in the domain \( x \geq -1 \), we can use the positive root). 2. Rearranging gives \( x = \sqrt{y} - 1 \). Therefore, the inverse function is: \[ f^{-1}(x) = \sqrt{x} - 1 \]

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy